Biblia dla dzieci w 365 opowiadaniach - Batchelor, Mary.; Haysom, John. (Lublin : [s.n.], 1991)
An illustrated collection of 365 Bible stories retold, from Genesis to Revelations. Translated from English. Ages 7-15.
Includes index.
Keywords: Bible stories, Polish -- Juvenile literature